2016
DOI: 10.1001/jamapsychiatry.2016.0501
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Compulsory Psychiatric Admissions

Abstract: The meta-analysis of the RCTs on advance statements showed a statistically significant and clinically relevant 23% reduction in compulsory admissions in adult psychiatric patients, whereas the meta-analyses of the RCTs on community treatment orders, compliance enhancement, and integrated treatment showed no evidence of such a reduction. To date, only 13 RCTs have used compulsory admissions as their primary or secondary outcome measure. This demonstrates the need for more research in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 35 publications
2
101
1
6
Order By: Relevance
“…However, these mixed results tend to offer more support for programs adapted to target patient subgroups than for the classic case management model. For compulsory outpatient treatment our review has found mixed evidence, although a recent systematic review shows that CTOs have no impact on compulsory admissions [92]. An encouraging result of our study is represented by the evidence that specific programs or interventions focusing on reducing readmission rates, whatever their focus might be (i.e.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, these mixed results tend to offer more support for programs adapted to target patient subgroups than for the classic case management model. For compulsory outpatient treatment our review has found mixed evidence, although a recent systematic review shows that CTOs have no impact on compulsory admissions [92]. An encouraging result of our study is represented by the evidence that specific programs or interventions focusing on reducing readmission rates, whatever their focus might be (i.e.…”
Section: Discussionmentioning
confidence: 75%
“…As a result, relevant papers for the topic of post-discharge factors associated with readmissions but focussing on a particular category of factors may have been missed in the search process. For example, the field of compulsory outpatient treatment is well developed, in the recent years several RCTs and systematic reviews having been conducted on this particular topic [92, 94]. Despite this, only five papers have been identified and included in our review.…”
Section: Discussionmentioning
confidence: 99%
“…Both are, and is likely to prove important in developing future interventions to reduce compulsion. 29 And whereas previous interventions to reduce compulsory admission have focused primarily on the individual (patient) level, such as Community Treatment Orders and enhanced care plans, 11 our findings suggestmean that interventions will need to operate at more than one spatial level to be effective.…”
Section: Interpretation Of Our Findingsmentioning
confidence: 74%
“…Orders and enhanced care plans, 11 our findings suggest that interventions will need to operate at more than one spatial level to be effective.…”
Section: Interpretation Of Our Findingsmentioning
confidence: 77%
See 1 more Smart Citation